Prosedur Dan Akibat Hukum Penundaan Kewajiban Pembayaran Utang Perseroan Terbatas (Studi Kasus Putusan Nomor 03/PKPU/2010/PN.Niaga.Sby) - Ni Nyoman Juliantini; I Made Arjaya; Ida Ayu Putu Widiati (Jurnal Analogi Hukum, 2021)
Suspension of debt payment obligation institutions (hereinafter abbreviated as PKPU) and Bankruptcy Institutions are two complementary institutions in an effort to regulate debt payments. These two institutions can be used by debtors who have difficulty paying their debts. In addition to being able to be used by debtors, these institutions can also be used by creditors, and agencies that are authorized by law act for and on behalf of creditors. One of the cases resolved with the PKPU process that was filed without the application for a bankruptcy statement submitted by the creditor was the case of Decision No. 03 / PKPU / 2010 / PN.Niaga.Sby PT. Nikki Puri. The formulation of the problem raised in this study is; (1) what is the procedure for requesting a delay in the obligation to pay debt to a limited liability company? And (2) what are the legal consequences of the decision to postpone debt repayment obligations? This study is a normative study with a legal, conceptual and case approach. Based on the results of the study it can be concluded that 1) The procedure for submitting a PKPU application can be carried out after the application for a bankrupt statement and without a request for a bankrupt statement, by completing formal and substantial requirements 2) The legal effect of the PKPU decision on the legal status of the debtor is the limitation in taking action on his assets, to creditors, namely the position of preferred creditors and separatist creditors to be the same as concurrent creditors, especially in carrying out collateral execution and debt collection.